2013
DOI: 10.1212/wnl.0b013e318293e310
|View full text |Cite
|
Sign up to set email alerts
|

Low-dose propranolol and exercise capacity in postural tachycardia syndrome

Abstract: Objective: To determine the effect of low-dose propranolol on maximal exercise capacity in patients with postural tachycardia syndrome (POTS). Methods:We compared the effect of placebo vs a single low dose of propranolol (20 mg) on peak oxygen consumption (VO 2 max), an established measure of exercise capacity, in 11 patients with POTS and 7 healthy subjects in a randomized, double-blind study. Subjects exercised on a semirecumbent bicycle, with increasing intervals of resistance to maximal effort.Results: Max… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(42 citation statements)
references
References 22 publications
1
41
0
Order By: Relevance
“…Taken together, our findings indicate the presence of a hyperadrenergic condition in lean females with POTS particularly while upright. This is in agreement with other studies (17,21,29,38,44), and our previous observations that POTS patients have an exaggerated decrease in BP induced by ganglionic blockade (30), and that the orthostatic tachycardia is responsive to ␤-blockade (4,46). We recognize that POTS is heterogeneous in presentation and pathophysiological mechanisms.…”
Section: Discussionsupporting
confidence: 93%
“…Taken together, our findings indicate the presence of a hyperadrenergic condition in lean females with POTS particularly while upright. This is in agreement with other studies (17,21,29,38,44), and our previous observations that POTS patients have an exaggerated decrease in BP induced by ganglionic blockade (30), and that the orthostatic tachycardia is responsive to ␤-blockade (4,46). We recognize that POTS is heterogeneous in presentation and pathophysiological mechanisms.…”
Section: Discussionsupporting
confidence: 93%
“…Some studies cited the use of beta-blockers [6,12,13,14,30,45], which can control the palpitations, and fludrocortisone, for plasma volume expansion and possible sensitization of the peripheral adrenergic receptors to catecholamines [6,12,13], as treatments of choice. Interestingly, low-dose propranolol was found to be more effective for the treatment of POTS symptoms [45,46] than metoprolol and high-dose propranolol, which controlled the heart rate but unexpectedly worsened the POTS symptoms [46]. Because of the improvement in symptoms, low-dose propranolol was found to improve exercise capacity in patients with POTS [45].…”
Section: Synthesis Of the Literaturementioning
confidence: 99%
“…Interestingly, low-dose propranolol was found to be more effective for the treatment of POTS symptoms [45,46] than metoprolol and high-dose propranolol, which controlled the heart rate but unexpectedly worsened the POTS symptoms [46]. Because of the improvement in symptoms, low-dose propranolol was found to improve exercise capacity in patients with POTS [45]. …”
Section: Synthesis Of the Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…Although this mechanism is most often associated with IAST, hyperadrenergic POTS has been described. Recent studies have demonstrated increased exercise capacity in POTS with use of low-dose propranolol [36,37]. POTS and IAST patients may be highly sensitive to beta-blockers and develop many side effects; thus these agents should be initiated at a low dose and titrated slowly.…”
Section: Therapymentioning
confidence: 99%